2012
DOI: 10.1016/j.cub.2012.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Direct Activation of Sleep-Promoting VLPO Neurons by Volatile Anesthetics Contributes to Anesthetic Hypnosis

Abstract: Summary Background Despite seventeen decades of continuous clinical use, the neuronal mechanisms through which volatile anesthetics act to produce unconsciousness remain obscure. One emerging possibility is that anesthetics exert their hypnotic effects by hijacking endogenous arousal circuits. A key sleep-promoting component of this circuitry is the ventrolateral preoptic nucleus (VLPO), a hypothalamic region containing both state-independent neurons and neurons that preferentially fire during natural sleep. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
182
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(195 citation statements)
references
References 48 publications
(75 reference statements)
13
182
0
Order By: Relevance
“…Blockade of either of these receptors inhibited CNO-facilitated emergence here, reciprocally validating that enhanced NE from LC-hM3Dq activation mediates accelerated emergence. Hypnotic doses of isoflurane have been shown to activate putative sleep-promoting ventrolateral preoptic (VLPO) area neurons; complementary to its excitatory actions in other regions, NE specifically hyperpolarizes the isoflurane-sensitive population of VLPO neurons (38). In the present study, we have shown that LC-NE activation also antagonizes induction of isoflurane anesthesia.…”
Section: Discussionsupporting
confidence: 52%
“…Blockade of either of these receptors inhibited CNO-facilitated emergence here, reciprocally validating that enhanced NE from LC-hM3Dq activation mediates accelerated emergence. Hypnotic doses of isoflurane have been shown to activate putative sleep-promoting ventrolateral preoptic (VLPO) area neurons; complementary to its excitatory actions in other regions, NE specifically hyperpolarizes the isoflurane-sensitive population of VLPO neurons (38). In the present study, we have shown that LC-NE activation also antagonizes induction of isoflurane anesthesia.…”
Section: Discussionsupporting
confidence: 52%
“…In accordance with previous reports, the VLPO PSP neurons were identified by their inhibitory response to bath application of NA (50 mM for 30 s) and were named as NA (-) neurons, whereas the neighboring neurons were excited by NA application (i.e. NA (ĂŸ) neurons) (Gallopin et al, 2005(Gallopin et al, , 2000Liu et al, 2013;Moore et al, 2012). The VLPO neurons were then recorded in whole-cell patch-clamp configuration, and their electrophysiological properties were analyzed in currentclamp mode.…”
Section: Resultsmentioning
confidence: 98%
“…The inhibition of these VLPO neurons by wake-promoting neurotransmitters is in agreement with their inactivity during wakefulness, and suggests that they should correspond to the sleep-active cells recorded in vivo and that are involved in the inhibition of arousal systems (Saper et al, 2001;Szymusiak et al, 1998). Henceforth, sleep-promoting neurons have been identified according to their inhibitory response to bath application of noradrenaline (NA) (Gallopin et al, 2005(Gallopin et al, , 2000Liu et al, 2013;Moore et al, 2012;Saint-Mleux et al, 2004;Varin et al, 2015). In contrast to other neurotransmitters that promote wakefulness, 5-HT was shown to induce opposite responses, as revealed by ex vivo electrophysiological recordings of presumed sleep-promoting (PSP) neurons in the rat VLPO.…”
Section: Introductionmentioning
confidence: 88%
“…Yet these lesions resulted in chronic sleep deprivation, suggesting the VLPO is still important for sleep homeostasis. Further electrophysiological studies have shown that isoflurane can directly activate the sleep-promoting VLPO neurons in the mammalian brain (Moore et al, 2012), and in the fly, acute activation of sleep-promoting neurons increases sleep and produces isoflurane hypersensitivity, whereas acutely blocking these fly neurons has the opposite effect . This indicates that there is a connection between sleep and general anesthesia in mammals and flies, yet it is clear that sleep pathways are not the sole mechanism for general anesthesia.…”
Section: Linking Sleep and General Anesthesia: The Curious Case Of Cmentioning
confidence: 99%